Occurrence of Trichinella spiralis in farmed wild boars (Sus scrofa): an underrated risk in China - Nian-Zhang Zhang; Meng Wang; Wei-Gang Chen; Wen-Yan Gai; Thanh Thi Ha Dao; Ting-Ting Li; Wen-Hui Li; Hai-Rui Zhang; Hong Yin; Nguyen Thi Bich Thuy; Bao-Quan Fu (Parasitology)
Natural infection by Trichinella sp. has been reported in humans and more than 150 species of animals, especially carnivorous and omnivorous mammals. Although the presence of Trichinella sp. infection in wild boars (Sus scrofa) has been documented worldwide, limited information is known about Trichinella circulation in farmed wild boars in China. This study intends to investigate the prevalence of Trichinella sp. in farmed wild boars in China. Seven hundred and sixty-one (761) muscle samples from farmed wild boars were collected in Jilin Province of China from 2017 to 2020. The diaphragm muscles were examined by artificial digestion method. The overall prevalence of Trichinella in farmed wild boars was 0.53% [95% confidence interval (CI): 0.51–0.55]. The average parasite loading was 0.076 ± 0.025 larvae per gram (lpg), and the highest burden was 0.21 lpg in a wild boar from Fusong city. Trichinella spiralis was the only species identified by multiplex polymerase chain reaction. The 5S rDNA inter-genic spacer region of Trichinella was amplified and sequenced. The results showed that the obtained sequence (GenBank accession number: OQ725583) shared 100% identity with the T. spiralis HLJ isolate (GenBank accession number: MH289505). Since the consumption of farmed wild boars is expected to increase in the future, these findings highlight the significance of developing exclusive guidelines for the processing of slaughtered farmed wild boar meat in China.